2015
DOI: 10.1016/j.vaccine.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Defense-in-depth by mucosally administered anti-HIV dimeric IgA2 and systemic IgG1 mAbs: Complete protection of rhesus monkeys from mucosal SHIV challenge

Abstract: Although IgA is the most abundantly produced immunoglobulin in humans, its role in preventing HIV-1 acquisition, which occurs mostly via mucosal routes, remains unclear. In our passive mucosal immunizations of rhesus macaques (RMs), the anti-HIV-1 neutralizing monoclonal antibody (nmAb) HGN194, given either as dimeric IgA1 (dIgA1) or dIgA2 intrarectally (i.r.), protected 83% or 17% of the RMs against i.r. simian-human immunodeficiency virus (SHIV) challenge, respectively. Data from the RV144 trial implied that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 46 publications
(71 reference statements)
6
82
0
Order By: Relevance
“…As the levels of anti-Env IgG but not those of anti-Env IgA in these secretions were associated with protection, our data suggest that nonneutralizing serum IgG (but not IgA) that transudates into vaginal tissues and secretions may play a significant role in preventing vaginal virus transmission. On the other hand, we postulate that even greater protection might perhaps be achieved if both mucosal IgA and serum IgG antibody responses can be induced (48).…”
Section: Discussionmentioning
confidence: 92%
“…As the levels of anti-Env IgG but not those of anti-Env IgA in these secretions were associated with protection, our data suggest that nonneutralizing serum IgG (but not IgA) that transudates into vaginal tissues and secretions may play a significant role in preventing vaginal virus transmission. On the other hand, we postulate that even greater protection might perhaps be achieved if both mucosal IgA and serum IgG antibody responses can be induced (48).…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, there is solid evidence that mucosal IgA could contribute to the prevention of HIV transmission. In a recent study, vaccine-elicited mucosal IgA responses were associated with protection against vaginal simian-human immunodeficiency virus (SHIV) challenge (14), and multiple investigations have demonstrated that passive rectal immunization with neutralizing dimeric IgA can protect from subsequent SHIV exposure (15,16). Similarly, we recently reported an association between a high magnitude of Env-specific IgA and low rates of breast milk HIV transmission (17).…”
mentioning
confidence: 87%
“…This is an important question to address in future studies. An elegant study by Ruprecht et al showed that rectal administration of an anti-HIV V3 recombinant dimeric human IgA2 monoclonal antibody (MAb), combined with systemic administration of the parental IgG1 MAb, was able to completely protect adult macaques against rectal SHIV-1157ipEL challenge, whereas passive immunization with only IgG1 or dIgA2 protected only 0% and 17% of macaques, respectively (65).…”
Section: Figmentioning
confidence: 99%